Comparative evaluation of the three different surface treatments - conventional, laser and Nano technology methods in enhancing the surface characteristics of commercially pure titanium discs and their effects on cell adhesion: An in vitro study - Vignesh; Sanjna Nayar; Bhuminathan; Mahadevan; S Santhosh (Wolters Kluwer Medknow Publications, 2015)
The surface area of the titanium dental implant materials can be increased by surface treatments without altering their shape and form, thereby increasing the biologic properties of the biomaterial. A good biomaterial helps in early cell adhesion and cell signaling. In this study, the commercially pure titanium surfaces were prepared to enable machined surfaces to form a control material and to be compared with sandblasted and acid-etched surfaces, laser treated surfaces and titanium dioxide (20 nm) Nano-particle coated surfaces. The surface elements were characterized. The biocompatibility was evaluated by cell culture in vitro using L929 fibroblasts. The results suggested that the titanium dioxide Nano-particle coated surfaces had good osteoconductivity and can be used as a potential method for coating the biomaterial.